O espaço como exercício de representação - Marisa, Cláudia (2017)
This paper proposes a phenomenological and aesthetic approach to “performative spaces”, suggesting implications and discussing various performative (real and fictional) places as scenic spaces of symbolic interaction. In doing so it confronts social-philosophical theories and multiple theatrical practices, proposing different ways to understand the concept of scenic space. It also questions performance art as an event that takes place between performers and spectators in a given space and time. In this process, embodiment is the structuring element of this new aesthetic behaviour.